Cover Feature: 2D MXenes as Perspective Immobilization Platforms for Design of Electrochemical Nanobiosensors (Electroanalysis 10/2019). Issue 10 (22nd October 2019) - Lorencova, Lenka; Gajdosova, Veronika; Hroncekova, Stefania; Bertok, Tomas; Blahutova, Jana; Vikartovska, Alica; Parrakova, Lucia; Gemeiner, Pavol; Kasak, Peter; Tkac, Jan
Abstract : 2D MXenes as Perspective Immobilization Platforms for Design of Electrochemical Nanobiosensors. More details can be found in the Full Paper by Lenca Lorencova et al. (DOI: 10.1002/elan.201900288).